Ammonia threshold for inhibition of anaerobic digestion of thin stillage and the importance of organic loading rate. Issue 2 (21st December 2015) - Moestedt, Jan; Müller, Bettina; Westerholm, Maria; Schnürer, Anna
Summary: Biogas production from nitrogen‐rich feedstock results in release of ammonia (NH3 ), causing inhibition of the microbial process. The reported threshold ammonia value for stable biogas production varies greatly between studies, probably because of differences in operating conditions. Moreover, it is often difficult to separate the effect of ammonia inhibition from that of organic loading rate (OLR), as these two factors are often interrelated. This study attempted to distinguish the effects of ammonia and OLR by analysis of two laboratory‐scale biogas reactors operating with thin stillage and subjected to an increase in free ammonia (from 0.30 to 1.1 g L −1 ) either by addition of an external nitrogen source (urea) or by increasing the OLR (3.2–6.0 g volatile solids L −1  d −1 ). The results showed that ammonia concentration was detrimental for process performance, with the threshold for stability in both processes identified as being about 1 g NH3‐N L −1, irrespective of OLR. Analysis of the methanogenic community showed limited differences between the two reactors on order level and a clear increase in the abundance of M ethanomicrobiales, particularly M ethanoculleus sp., in response to increasing ammonia concentration. Further comprehensive molecular analysis revealed that diverse M ethanoculleus species dominated in the reactors at a given ammonia level at different OLR. The acetogenic community was clearly affected by both ammonia concentration and OLR, suggesting that the volatile fatty acid load in relation to the higher OLR was important for the dynamics of this community. Abstract : This study attempted to distinguish the effects of ammonia and OLR by analysis of two laboratory‐scale biogas reactors operating with thin stillage and subjected to an increase in free ammonia (from 0.30 to 1.1 g/L) either by addition of an external nitrogen source (urea) or by increasing the OLR (3.2‐6.0 g volatile solids/L d). The results showed that ammonia concentration was detrimental for process performance, with the threshold for stability in both processes identified as being about 1 g NH3‐N/L, irrespective of OLR.